Implementasi Project Based Learning dalam Menstimulasi Kreativitas Peserta Didik di PAUD SKB Mojoagung - Sabita, Adani Alya; Artha, I Ketut Atmaja Johny (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
Project-Based Learning has become an increasingly popular approach in early childhood education because of its potential to stimulate creativity, and active learning through projects that are interesting and relevant to everyday life. The focus of the research concerns the implementation, inhibiting and supporting factors for the implementation of project-based learning centers that play a role in stimulating the creativity of PAUD SKB Mojoagung students. The aim of this research is to analyze the implementation of PjBL in stimulating students' creativity. This research uses a qualitative approach. Data was obtained using participant observation techniques, in-depth interviews and documentation. The research results show that educators and parents ensure that students have access to adequate resources so as to support the process of stimulating their creativity. Inhibiting factors include limited funding allocations related to providing outdoor activities, lack of updating experimental equipment, limited educational resources. Supporting factors include students' enthusiasm for playing a professional role, extensive playing infrastructure, availability of APE such as costumes and playing equipment. Keywords: Project-based Learning, Stimulation of creativity, Early-childhood